2016
DOI: 10.1111/apa.13354
|View full text |Cite
|
Sign up to set email alerts
|

Bed‐sharing by breastfeeding mothers: who bed‐shares and what is the relationship with breastfeeding duration?

Abstract: Aim: To explore the link between breastfeeding duration and bed-sharing frequency among women reporting a prenatal intention to breastfeed.Methods: About 870 participants in a randomised breastfeeding trial, recruited at midpregnancy, provided weekly snapshots of breastfeeding and bed-sharing behaviour for 26 weeks following birth. Strength of prenatal breastfeeding intent was recorded at recruitment using Likert-type scales.Results: Outcomes were frequency of bed-sharing at home for at least one hour per week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 25 publications
4
59
0
1
Order By: Relevance
“…As expected, bed sharing was significantly associated with breastfeeding, which has been found in several other studies 13, 19. Bed sharing facilitates breastfeeding, which makes it an attractive option for women who want to breastfeed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, bed sharing was significantly associated with breastfeeding, which has been found in several other studies 13, 19. Bed sharing facilitates breastfeeding, which makes it an attractive option for women who want to breastfeed.…”
Section: Discussionsupporting
confidence: 87%
“…In view of the current discussions concerning the possible hazards associated with bed sharing 19, 20, 21, 22, 23, 24, we need to obtain more detailed knowledge on how families bed share and to what extent methods for the so‐called safe bed sharing, or safer bed sharing 24, 25, are used.…”
Section: Discussionmentioning
confidence: 99%
“…204 Although bed-sharing may facilitate breastfeeding, 175 there are other factors, such as intent, that influence successful breastfeeding. 205 Furthermore, 1 case-control study found that the risk of SIDS while bedsharing was similar among infants in the first 4 months of life, regardless of breastfeeding status, implying that the benefits of breastfeeding do not outweigh the increased risk associated with bed-sharing for younger infants. 194 The risk of bed-sharing is higher the longer the duration of bed-sharing during the night, 91 especially when associated with other risks.…”
Section: Figurementioning
confidence: 99%
“…Blacks, American Indians/Alaskan Natives (AIs/ANs), New Zealand Māori, Australian Aborigines, indigenous Canadians, and low‐income British people (see below). In this paper, we draw on anthropological and social epidemiological insights to argue that instead of this individualistic approach, we need to consider the social origins, clustering or co‐occurrence, and interplay of known risk factors (Ball et al, ; Singer, Bulled, Ostrach, & Mendenhall, ) in order to make progress in reducing infant deaths in high‐risk populations.…”
Section: Introductionmentioning
confidence: 99%
“…Sofa sharing poses far greater risk than sleeping next to an infant in an adult bed (Moon & Task Force On Sudden Infant Death, ). Because bedsharing facilitates breastfeeding and is associated with greater breastfeeding duration (Ball et al, ; Huang et al, ; J. McKenna, Mosko, & Richard, ), advice against bedsharing also has profound implications for the health of both women and children (Bartick et al, ; Victora et al, ). In response to a systematic assessment of the evidence, the United Kingdom has issued guidance that emphasizes the risks of smoking and sofa sharing, prioritizes room sharing, and encourages a contextual, informed choice approach about bedsharing (Ball, ).…”
Section: Introductionmentioning
confidence: 99%